Draft genome sequence of marine alphaproteobacterial strain HIMB11, the first cultivated representative of a unique lineage within the Roseobacter clade possessing an unusually small genome. Issue 3 (November 2014) - Durham, Bryndan; Grote, Jana; Whittaker, Kerry; Bender, Sara; Luo, Haiwei; Grim, Sharon; Brown, Julia; Casey, John; Dron, Antony; Florez-Leiva, Lennin; Krupke, Andreas; Luria, Catherine; et al.
Abstract Strain HIMB11 is a planktonic marine bacterium isolated from coastal seawater in Kaneohe Bay, Oahu, Hawaii belonging to the ubiquitous and versatileRoseobacter clade of the alphaproteobacterial familyRhodobacteraceae . Here we describe the preliminary characteristics of strain HIMB11, including annotation of the draft genome sequence and comparative genomic analysis with other members of theRoseobacter lineage. The 3, 098, 747 bp draft genome is arranged in 34 contigs and contains 3, 183 protein-coding genes and 54 RNA genes. Phylogenomic and 16S rRNA gene analyses indicate that HIMB11 represents a unique sublineage within theRoseobacter clade. Comparison with other publicly available genome sequences from members of theRoseobacter lineage reveals that strain HIMB11 has the genomic potential to utilize a wide variety of energy sources (e.g. organic matter, reduced inorganic sulfur, light, carbon monoxide), while possessing a reduced number of substrate transporters.